Limitation of liability and reinsurance and its role in increasing production insurance: بحث أستطلاعي في شركة التامين العراقية العامة (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The liability limit liability limit and reinsurance re factors insurance are important in influencing the achievement of company's competitive goals and achieve success and excellence in the market and because the limit of liability and reinsurance aimed to increase output with the stability of inputs leading to increased insurance business and increase profits. The study was based on two variables presidents interact with each other to form the intellectual and philosophical framework has two ( the limit of liability and reinsurance ) . The study was launched from a problem expressed by a number of targeted questions answered from the elucidation of theoretical philosophy and intellectual goals of these variables and highlight the importance of the role played by each of the limit of liability and reinsurance to influence the company's business and achieve success . It was selected as the Iraqi insurance company as a sample for the study, and were gathering information in the form of a time series that spanned between ( 2010_ 2014) And extract the averages of both premiums and compensations , and compare the premiums for damages to know the company's share of its business and goes off for a company of special public insurance premiums , and measuring the ratio of compensation and share -off companies, including to allow us to see if the company is able to increase the responsibility of its business or edit replays agreement to fit and future plans . In light of the results obtained , the study found a group of the most important conclusions :• that there is a strong correlation between the reinsurance agreement limit liability where the basis of the agreement is the value of the loss and therefore be in the company husban advance as far as may be exposed his losses.• The insurance companies take into account when determining the limit of liability : Distribution determine the probability of total loss and determine the company's ability to cope with losses Sheibany and and determine the probability that the total losses exceed reserves.- Determine responsibility , which is determined on the basis of the maximum total losses of the company can be borne in light of the possibility of the destruction of the company that puts the decision-maker so that the company is working in his shadow , and is determined as follows: the limit of liability is the value that check tie between : Maximum total losses of the portfolioLosses ceded reinsurance = Alaanaati- for more than the limit of liability premiums.And the effect of these conclusions was to put some of the recommendations was the most important :When you begin to determine the limit of liability of the company 's senior management to determine :A- predict and design the probabilistic distribution plan for the total expected losses in the future.(B) identify all the resources that can be used to pay off the losses Sheibany foremost of which is : ( premiums , allowances , reserves , retained earnings ) .. etc